Análisis heterótico sobre caracteres fenotípicos de progenies F1 derivados de cruzamientos entre el progenitor Br-101-UTB con 10 cultivares de Arroz (Oriza sativa L. spp. indica) - Amat Cabrera, Jonathan Jacobo (2019)
The essay was carried out in the Experimental Farm El Palmar of the Technical University of Babahoyo. CEDEGE project, province of Los Ríos. The Objectives were the following: To determine the hybrid vigor or heterosis in segregating F1 populations, derived from the parent Br-101-UTB, used as both male and female parental, in combination with 10 parents. Analyze the heterotic levels that are inherited on the phenotypic characters of F1 progenies derived from crosses between the Br-101-UTB progenitor with 10 indica-type rice cultivars and select the progenies of better agronomic behavior and production, in terms of hybrid vigor. Twenty F1 populations of indica-type rice were evaluated, provided by the Biotechnology Laboratory of the Faculty of Agricultural Sciences of the UTB. The seventeen variables evaluated were statistically analyzed through measures of central tendency (mean and mode), measures of dispersion (variance and standard deviation), in addition; frequency distribution tables, histograms and / or frequency polygons were made. The estimation of Heterosis (H) expressed in terms of percentage, was made based on the following formula: H=(F1-(P1+P2)/2)/( (P1+P2)/2) x 100 In the present experimental work, a total of 17 agronomic variables were evaluated. According to the results obtained, and based on the objectives proposed in the present investigation, the following conclusions are issued: 85% (17/20) of the F1 populations showed positive heterosis values for the variable grain yield per plant , regarding the characteristic of sheared grain length (mm), 15% (3/20) of the F1 populations stood out for showing extra-long grains (> 7.5 mm), while 85% (17/20 ) of the F1 populations studied, are considered long grain, because they maintain their length between (6.61 - 7.5 mm). In the variables days to flowering and length of grain without husk, the best results were obtained, since all the F1 populations evaluated showed outstanding percentages of heterosis, as far as the vegetative cycle is concerned, it was observed that all the F1 populations studied were characterized because they are considered “intermediate” with respect to this variable, and finally with regard to the plant height variable, it was observed in all the F1 populations evaluated, that the greatest growth was expressed between 40 and 60 days after transplantation , with an average of 33.9 cm of growth.